Molecular factors associated with virulence of marine vibrios isolated from striped bass in Chesapeake Bay. - Toranzo, A E (1983)
On the basis of cultural and biochemical properties as well as DNA homology assays, 81 Vibrio strains isolated from diseased striped bass and from Chesapeake Bay water were assigned to eight distinct groups. All organisms belonging to two of the groups were pathogenic for striped bass and were identified as Vibrio anguillarum, whereas organisms classified in the other six groups were nonpathogenic and were designated as Vibrio spp. Unlike the pathogenic V. anguillarum strain 775 isolated in the Pacific Northwest, strains pathogenic for striped bass did not contain any plasmids; however, they were similar to the Northwest isolates in that virulence was correlated with their ability to grow in the presence of nonimmune striped bass serum or under conditions of iron limitation. Sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis of outer membranes showed that additional proteins were induced in those organisms capable of growth under conditions of iron limitation. It was of interest that 22 of the nonpathogenic isolates harbored one or more plasmids which, by restriction endonuclease analyses, were shown to be clearly different from the virulence plasmid pJM1.